Kesetaraan Gender dalam Cerita Putri Mandalika Analisis Tzvetan Todorov - Desak Made Yoniartini (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
Literary work is something special for both the connoisseur and the creator. There are not many literary works that discuss gender equality, this is interesting to research, one of the works that discuss gender equality is the story of Putri Mandalika which is closely related to the